PERLINDUNGAN HUKUM DAN KEDUDUKAN PEMEGANG HAK TERHADAP PEMBLOKIRAN SERTIFIKAT HAK ATAS TANAH OLEH KANTOR PERTANAHAN - Jazillatul Ulfa; Fitika Andraini (Jurnal Ilmiah Dinamika Hukum, 2020)
Earth, water and space as well as the natural resources contained therein under the control of the State are gifts from God Almighty whose functions and uses are for the prosperity of the people. Land for the Indonesian Nation is a source of livelihood and is regulated in the provisions of the Law. The Basic Agrarian Law No. 5 of 1990 lays the foundation on providing legal certainty for land rights for the Indonesian people. Legal certainty is obtained after the land registration process. Land rights that have legal certainty can be transferred or transferred. however, in the process, disputes over land rights still occur in the community. Blocking of Land Rights Certificates is taken as an administrative step in the dispute resolution process, but there is a period of only 30 days to record the blocking of Peru, it is known how the factors of land blocking, how to know the position of the holder of the Land Rights certificate when the block is being blocked and when the period is 30 blocking day is over but the dispute has not been resolved. The type of research used by the writer is juridical normative and descriptive analytical research specification by collecting data by means of literature study and interviews which are presented in a descriptive manner and analyzed in a descriptive qualitative manner. The results of the research and data analysis carried out show the factors that cause the blocking of Land Rights Certificates, namely: a. Gono-Gini distribution of assets, b. Land Rights Holders do not have good faith, c. Distribution of Inheritance, d. Lost Certificate, e. There is an investigation by the Police, f. Land rights confiscated by the State Receivables Affairs Committee (PUPN) in connection with the settlement of State Receivables. Legal protection & the position of the Land Rights Certificate Holder when the blockage is carried out is that the right holder cannot take legal action against the blocked land for 30 days after the block registration was carried out, article 19 UUUPA / PP 241997 regarding registration will not be lost The legal certainty of the rights holder remains attached to it as long as there has been no transfer of rights to the land they own. If the 30 day period of blocking is over but the dispute has not been completed, the blocking will not be removed by law and will remain in effect as long as there is no request for revocation by the applicant or the provisions -Other provisions which become the reasons for the removal of the block in accordance with article 14 of the Regulation of the Minister of ATR / Head of the National Land Agency No.13 of 2017 concerning the Procedure for Blocking and Confiscation, this is because in the Land Office (Semarang) there is no system that can identify or filter out expired blocks. Keywords: Land Registration, Legal Certainty, Rightsholders, Blocking of Land Rights Certificates, Position of Rightsholders